Petrographic Characterization of Selected Sidewall Core Samples from NG-1 Well, Niger Delta, Nigeria: Palaeoclimatic Implication - Odedede, O. (Journal of Scientific Research, 2019)
Petrographic investigation of sandstones from Agbada Formation in NG-1 well was undertaken in order to petrographically characterize the sandstones. Petrographic examination of the sandstone shows that the sandstones are mineralogically mature and poorly to moderately sorted quartz arenite. Compositionally, made up of monocrystalline quartz (90-96%), polycrystalline quartz (7-2%), feldspar (2-5%), rock fragments < 3%, silica, hematite cement and clay matrix. Abundant of monocrystalline quartz with marginal undulose extinction over polycrystalline quartz suggest igneous source derivatives. Presence of close packing, point and concavo – convex contacts, weathered plagioclase feldspar, grain dissolution, and fabric imprints indicates intermediate diagenesis. Consideration of petrographic attributes and paleoclimatic discrimination plot inferred semi-humid to humid palaeoclimates.